Water rights issues in agriculture - Meinzen-Dick, Ruth S. (International Water Management Institute, 2002)
In the water sector we are seeing more attention to water rights in response to greater competition for the resource and greater expectations of farmers’ roles in managing water. The scarcity and competition come not only from greater demand for irrigation, but also from greater demand from other water uses, especially cities and industries that are often drawing water away from agriculture. Clear water rights can reduce conflicts over the resource in such contexts. Expectations of farmers’ roles in water management have increased through irrigation management transfer programs in which the government transfers responsibility for operating and maintaining irrigation systems to farmers’ associations. Without clear rights over water, farmers often lack the incentive and authority to invest the necessary time and resources for such management responsibilities. It is therefore appropriate that we should give more attention to water rights in many countries. The question is what types of water rights are appropriate for each context, and what can be done to support such rights. Policymakers and advisors that recognize a need for secure water rights often think that it is a matter of passing the “right” law—often borrowed from another country. This approach suffers from two major problems. First, state law does not by itself define water rights. Customary, religious and other types of law are also very important. Second, what may work well in one country or context will not necessarily apply in another, where physical and socioeconomic conditions are different, including different backgrounds on water rights. What is needed is a more flexible approach, adaptable to local conditions. This paper describes key factors for understanding water rights. This includes recognizing the multiple sources of water rights (legal pluralism) and the bundles of rights that different stakeholders can have. It concludes with implications for water rights policy or reform processes.